Commodity price risk management and fiscal policy in a sovereign default model - Bernabe Lopez-Martin; Julio Leal; André Martínez Fritscher (Banco de México, 2017)
Commodity prices are an important driver of fiscal policy and the business cycle in many developing economies. We analyze a dynamic stochastic small-open-economy model of sovereign default, featuring endogenous fiscal policy and stochastic commodity revenues. The model accounts for a positive correlation of commodity revenues with government expenditures and a negative correlation with tax rates. We quantitatively document the extent to which the utilization of different financial hedging instruments by the government contributes to lowering the volatility of different macroeconomic variables and their correlation with commodity revenues. An event analysis illustrates how financial hedging instruments moderate fiscal adjustment in response to significant falls in the price of commodities.
Keywords: F34; F41; F44; 330; commodity revenues; hedging; indexed bonds; fiscal policy; sovereign default